A ação policial e os direitos humanos : pesquisa sobre valores e atitudes de policiais militares paranaenses - Tordoro, Marcos Antonio (2014)
Human rights were not born in a particular time and its historical inaccuracy is discussed by many authors. However, in this complex process of arising, human rights gain more evidence from the creation of the United Nations and the Universal Declaration of Human Rights of 1948. These rights are disrespected for centuries. In the Brazilian context, the deployment and the actions of the authoritarian regime of military dictatorship, as well as other ages of the past and contemporary, they mark the violent and truculent trend of our country, especially in the military police forces of the states. The heritage of authoritarianism is printed in the values and attitudes of the population and in particular on the police officers. Likewise, in many Latin American countries, many police forces show a huge heritage of authoritarian regimes that ruled under the empire of arbitrariness and violence, with caveats to the Chile and Colombia that although has passed through the authoritarianism, nowadays they own police forces that inspire confidence in their populations, with policing programs of proximity, in other words, public policies to integrate the police to the community, with transparency and focus on prevention. To understand the perceptions of the military police officers of Paraná about the human rights, based on a national survey held in 2008 which showed that the Brazilian population has a violent tendency and accepts arbitrary practices, was held in 2013, a survey which showed that the police officers searched, they reproduce the trend of the population, but their attitudes and values of disrespect for human rights are potentiated because of the informal rules of corporatism and the feeling of police inefficiency when human rights are respected. Researches of this nature are not common, mostly when studying military police in the Brazilian context, this complex process of sedimentation of human rights in Latin American culture. The research aims to contribute to the elucidation of some unknown questions about the respect of the human dignity by the security agents, in the execution of its constitutional mission and, amid the historical contents of human rights issues in Brazil and in the world , to human rights education and the factors that enhance the denial of these rights, the survey data were analyzed and they translated that the attitude and the behavior of the military police officers of Paraná, in relation to human rights, is denial.